Horizontal Wall Movement and Ground Surface Settlement Analysis of Braced Excavation Based on Support Spacing - Wirman Hidayat (Kadiri University, 2021)
Lateral supports, including walls and bracing systems on deep excavation, are generally required to prevent excessive horizontal wall movement and ground surface settlement which can cause damage to the excavation construction itself and adjacent structures. These criteria are influenced by the stiffness of the excavation system, including the spacing of vertical and horizontal supports (struts). This paper presents the parametric study using the variation of struts spacing in the vertical and horizontal direction to analyze the influence on horizontal wall movement and ground surface settlement. The analysis was carried out using finite element software, PLAXIS performed in 2D plain strain and 3D. This study shows that struts spacing in the horizontal and vertical direction is equally important and equally significant on the deformation that occurs with a maximum difference of about 0.06%. The maximum horizontal wall movement ratio computed by 3D analysis to the 2D analysis is defined as plain strain ratio (PSR). The PSR value decreases when the system stiffness is decreased. Meanwhile, when the system stiffness was higher, the PSR value will be higher and closer to 1, showing that the difference in the 3D and 2D models is relatively small.